Studying HLA class I polymorphism in brain tumour patients (Baghdad Science Journal, 2012)
The present study aimed at shed light on the association between HLA-class I antigens (A, B and Cw) and brain tumours (meningioma and glioma) in the basis of their individual frequencies or two-locus association A total of 52 brain tumour patients were enrolled in this study, with an age range of 7-68 years. The patients were divided into two clinical groups; meningioma (20 cases) and glioma (22 cases), while the remaining 10 cases represented other types of brain tumour. Control samples included 47 Iraqi Arab apparently healthy blood volunteers, with an age range of 15-50 year. Three HLA antigens showed a significant increased frequency in total patients as compared to controls. They were B13 (34.6 vs. 6.5%), B40 (15.4 vs. 2.2%) and Cw3 (15.4 vs. 2.2%). In contrast, B5 was significantly decreased (15.4 vs. 34.8%). In meningioma patients, only B13 was significantly increased (35.0 vs. 6.5%), while in glioma patients, B13 (36.4 vs. 6.5%) and Cw5 (36.4 vs. 2.2%) were significantly increased. Variations between patients and controls have been also encountered for the observed and expected HLA-two locus associations (B13-Cw3, B13-Cw5 and B40-Cw5).